Vitreoretinal surgery using bromphenol blue as a vital stain: evaluation of staining characteristics in humans. Issue 9 (21st February 2007) - Haritoglou, Christos; Schumann, Ricarda G; Strauss, Rupert; Priglinger, Siegfried G; Neubauer, Aljoscha S; Kampik, Anselm
Abstract : Objective: To evaluate the staining characteristics of bromphenol blue used during vitreoretinal surgery in humans. Patients and methods: 13 patients with epiretinal membranes were included. Before and after surgery a complete clinical examination including best corrected visual acuity, funduscopy, fluorescein angiography, OCT (Stratus), Goldmann perimetry and multifocal ERG as well as photography of the macular area was performed. Bromphenol blue was used in concentrations of 0.2% in most patients. Removed epiretinal tissue was evaluated using electron microscopy. Results: Using dye concentrations of 0.2% a good demarcation of epiretinal membranes was seen in 11/13 patients. Staining of vitreous remnants at the vitreous base was seen in all patients. No dye-related adverse events were seen during follow-up in the functional tests (VA, ERG, perimetry) performed. Histological evaluation of epiretinal membranes showed unremarkable aspects of epiretinal cellular layers and unremarkable retinal surface of the internal limiting membrane (ILM). Conclusion: Bromphenol blue appears to be a very helpful and safe tool in posterior segment surgery. The staining characteristics need to be further evaluated in prospective study settings and larger numbers of patients.